2003
DOI: 10.1038/sj.gene.6364004
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 promoter polymorphisms influence disease severity and course in psoriasis

Abstract: We analyzed three single-nucleotide polymorphisms (SNPs) at the interleukin-10 (IL-10) 5 0 flanking region (positions À1082 A/ G, À819 C/T and À592 C/A) in an association case-control study involving 248 patients with plaque type of psoriasis and 148 unrelated healthy volunteers using ARMS (amplification refractory mutation system)-PCR (Polymerase Chain Reaction) method. No difference was found in the frequencies of haplotype distribution between healthy controls and patients with psoriasis. There were no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 16 publications
(25 reference statements)
3
39
1
1
Order By: Relevance
“…In some instances, however, the removal of IL-10 during an infection results in inflammation-associated death, highlighting the critical immunosuppressive role of IL-10 in vivo. Polymorphisms in the human IL-10 promoter have also been linked to altered susceptibility (35,40,66,85,98,107), supporting the findings in animal models. In general, the absence of IL-10 leads to extended survival after infection that is associated with an enhanced adaptive immune response, including CD4 T cell IFN-␥ production and improved control of infection as the normal proinflammatory responses are extended or enhanced.…”
Section: The Absence Of Il-10 Leads To Improved Control Of Infectionsupporting
confidence: 67%
“…In some instances, however, the removal of IL-10 during an infection results in inflammation-associated death, highlighting the critical immunosuppressive role of IL-10 in vivo. Polymorphisms in the human IL-10 promoter have also been linked to altered susceptibility (35,40,66,85,98,107), supporting the findings in animal models. In general, the absence of IL-10 leads to extended survival after infection that is associated with an enhanced adaptive immune response, including CD4 T cell IFN-␥ production and improved control of infection as the normal proinflammatory responses are extended or enhanced.…”
Section: The Absence Of Il-10 Leads To Improved Control Of Infectionsupporting
confidence: 67%
“…19 We demonstrated previously that IL-10 promoter polymorphisms influence clinical course of plaque-type psoriasis. 20 Hensen et al 21 observed the protective effect of the microsatellite marker IL-10.G9 allele 3 from the IL-10 promoter region to familial psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…97 Protective effects conferred by some alleles and haplotypes within this cluster of genes has also been proposed, along with suggestions that some alleles influence severity or clinical course of disease. 98,99 A comprehensive association analysis of alleles and haplotypes within this cluster of genes is warranted in other patient populations.…”
mentioning
confidence: 99%